SOME FEATURES OF AVIATION CRIMES DURING MARTIAL TIME - Lykhova, Sofiia; Semchuk, Natalya (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The purpose of this article is to analyze aviation crimes in martial time and develop theoretical and practical recommendations to combat this phenomenon. Methods: general and special scientific methods were used to achieve this purpose. The use of these methods allowed to outline the problems of combating of aviation crimes from a criminal law point of view and to offer practical recommendations for combating this phenomenon. Results: during the preparation of the article, martial state was declared in Ukraine in connection with the attack of the Russian Federation. Contrary to international law, Russia has not officially declared war on Ukraine. In Ukraine war crimes introduced additional responsibility only for the Ukrainian military, there are special features of qualification. As Ukraine has now closed the airspace to all aircraft except Ukrainian state military aircraft, all Russian military pilots who perform combat sorties in Ukrainian airspace are liable both as ordinary airspace violators and as criminals against humanity. The article considers 3 main situations of war aviation crimes: investigation; flight with ammunition; bombing of non-residential buildings and bombing of civilian objects from the point of view of the criminal law and given practical recommendations on the possible qualification of such actions under the laws of Ukraine.